2020
DOI: 10.3389/fmicb.2020.597529
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ELISA, Immunofluorescence, and Lateral Flow Assay for SARS-CoV-2 Serologic Assays

Abstract: BackgroundThe SARS-CoV-2 outbreak has emerged at the end of 2019. Aside from the detection of viral genome with specific RT-PCR, there is a growing need for reliable determination of the serological status. We aimed at evaluating five SARS-CoV-2 serology assays.MethodsAn in-house immunofluorescence assay (IFA), two ELISA kits (EUROIMMUN® ELISA SARS-CoV-2 IgG and NovaLisa® SARS-CoV-2 IgG and IgM) and two lateral flow assays (T-Tek® SARS-CoV-2 IgG/IgM Antibody Test Kit and Sure Bio-tech® SARS-CoV-2 IgM/IgG Antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 34 publications
1
54
0
Order By: Relevance
“…NovaLisa showed comparable IgG sensitivity to other studies, 81.5% vs. 89.7% after two weeks post symptoms onset, and 90.0% vs. 91.2% after one month [35]. The IgM sensitivity for NovaLisa was higher in our study after two weeks (54.2% vs. 30.8%), but it significantly dropped after this (12.8% after one month vs. 38.2% after three weeks) [35,36]. This could be because many samples (~67%) collected at this time-interval were from asymptomatic patients whose samples were collected between 30 and 98 days post positive SARS-CoV-2 RT-PCR test.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…NovaLisa showed comparable IgG sensitivity to other studies, 81.5% vs. 89.7% after two weeks post symptoms onset, and 90.0% vs. 91.2% after one month [35]. The IgM sensitivity for NovaLisa was higher in our study after two weeks (54.2% vs. 30.8%), but it significantly dropped after this (12.8% after one month vs. 38.2% after three weeks) [35,36]. This could be because many samples (~67%) collected at this time-interval were from asymptomatic patients whose samples were collected between 30 and 98 days post positive SARS-CoV-2 RT-PCR test.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies reported slightly better IgG sensitivity results for EDI and DiaPro; 76.1% vs. 82.7% for EDI and 53.5% vs. 92.2% for DiaPro [34]. NovaLisa showed comparable IgG sensitivity to other studies, 81.5% vs. 89.7% after two weeks post symptoms onset, and 90.0% vs. 91.2% after one month [35]. The IgM sensitivity for NovaLisa was higher in our study after two weeks (54.2% vs. 30.8%), but it significantly dropped after this (12.8% after one month vs. 38.2% after three weeks) [35,36].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Results from this Two-In-One LFIA assay identified antibodies generated by mice immunized with membrane glycoprotein that did not cross-react to the hemagglutinin of SD/H1N1-S-OIV. However, since the amino acid sequence of membrane glycoprotein of SARS-CoV-2 shares high identity to other strains of the β-coronaviruses, false positive results [ 29 ] may appear on CFIAs due to previous exposure to closely-related β-coronaviruses. Spotting membrane glycoproteins from various β-coronaviruses on a CFIA may improve the viral specificity of detecting antibodies to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-based tests like serological tests and viral antigen detection have been reported as alternative diagnostic tests which could detect both MERS-CoV and SARS-CoV-2 [16] , [17] , [183] , [184] , [185] , [186] , [26] , [32] , [35] , [123] , [179] , [180] , [181] , [182] . Generally, compared to nucleic acid-based detection tests, the protein-based test can be less sensitive as it does not involve target amplification [185] , and there is a higher possibility of getting false-positive results [183] .…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%